Trends in the valence band electronic structures of mixed uranium oxides. Issue 70 (15th August 2018) - Kvashnina, Kristina O.; Kowalski, Piotr M.; Butorin, Sergei M.; Leinders, Gregory; Pakarinen, Janne; Bès, René; Li, Haijian; Verwerft, Marc
Abstract : The valence band electronic structures of mixed uranium oxides (UO2, U4 O9, U3 O7, U3 O8, and β-UO3 ) have been studied using the resonant inelastic X-ray scattering (RIXS) technique at the U M5 edge and computational methods. Abstract : The valence band electronic structures of mixed uranium oxides (UO2, U4 O9, U3 O7, U3 O8, and β-UO3 ) have been studied using the resonant inelastic X-ray scattering (RIXS) technique at the U M5 edge and computational methods. We show here that the RIXS technique and recorded U 5f–O 2p charge transfer excitations can be used to test the validity of theoretical approximations.